School operational assistance in basic education: Organizational responses to policy complexities - Perdana, Novrian Satria; Subarsono, Agustinus; Pitoyo, Agus Joko; Utomo, Puguh Prasetya (Conscientia Beam, 2023)
This study aims to analyze variations in school responses in dealing with the complexities of School Operational Assistance (SOA) policy implementation. Several policies that gave rise to complexity in this study were included such as the policy of transferring SOA funds directly to schools, the policy of implementing the remaining SOA funds as a deduction for the following year's SOA funds, the policy of spending based on the Procurement Information System in Schools, and the policy of financial planning and reporting based on the School Activity Plan and Budget Application. The sample for this study consisted of 24 schools consisting of elementary and junior high schools that had remaining SOA funds for 2019-2021 in Yogyakarta City, Sleman Regency, and Gunung Kidul Regency. This research is qualitative research using interview techniques with school principals, SOA treasurers, and senior teachers. The data obtained were processed using the NVivo qualitative software. Based on the results of processing data sourced from interviews, there are three variations of school responses in dealing with policy complexities, namely acquiesce, compromise, and adjustment. The novelty of this study is the emergence of an adjustment response. The results of this study have an impact on policy makers so that in formulating policies it is necessary to look at old policies that are still valid so that policy actors do not experience a dilemma. © 2023 Conscientia Beam. All Rights Reserved.